Sacramental dimension and catholic celebration of marriage: canonical requests to access marriage - Peña García, Carmen (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2016)
Current society, marked with an increase of unfaithful baptized, people indifferent to religion and immersed in irregular marriage situations, awakes a particular pastoral call which demands special care when preparing couples for marriage and their access to Catholic celebration. This study, from a canonical perspective, intends to offer an overview on the sacrament of marriage. It focuses on the requests concerning preparation and admission to canonical marriage: Is faith needed to celebrate the sacrament of marriage? Which is the role of ecclesiastical authorities concerning the criteria to admit a couple to a canonical marriage celebration?
Keywords: Sacrament of marriage; faith; preparation for marriage; previous investigations; examination of the spouses.